Internet based teleoperation for cooperative navigation and manipulation - Petrović, Ivan (Strojniški vestnik, 2009)
The Internet is a very fast evolving new technology, allowing people to electronically connect to places that are thousands of miles apart. By combining network technologies with the capabilities of mobile robots and manipulators, Internet users can discover and physically interact with far-away places thereby, creating opportunities of resource sharing, remote experimentation and long-distance learning. This paper presents a general concept of Internet based teleoperation, which structures a teleoperation system into three layers. The concept was applied in developing a teleoperation system that enables two human operators to safely control two cooperative mobile robots in unknown and dynamic environments from any two PCs connected to the Internet by installing a developed client program on them and by using simple force feedback joy sticks. On graphical user interfaces, the operators receive images forwarded by the cameras mounted on robots, and on the joysticks they can feel forces forwarded by developed obstacle prevention algorithm based on the dynamic window approach. To overcome the instability caused by the unknown and varying time delay an event-based teleoperation method is employed to synchronize actions of each robot with commands from its operator. Through experimental investigation it is confirmed that developed teleoperation system enables the operators to successfully accomplish cooperative navigation and manipulation tasks in complex environments.
Keywords: telecommunication; telekomunikacije; internet; teleoperacija; navigacija; robotika